Clinical Features, Diagnosis, and Treatment of COVID-19 in Hospitalized Patients: A Systematic Review of Case Reports and Case Series - Tahvildari, Azin; Arbabi, Mahta; Farsi, Yeganeh; Jamshidi, Parnian; Hasanzadeh, Saba; Calcagno, Tess Moore; Nasiri, Mohammad Javad; Mirsaeidi, Mehdi (Frontiers in Medicine, 2020)
Introduction: The 2019 novel coronavirus (COVID-19) has been declared a public health emergency worldwide. The objective of this systematic review was to characterize the clinical, diagnostic, and treatment characteristics of hospitalized patients presenting with COVID-19. Methods: We conducted a structured search using PubMed/Medline, Embase, and Web of Science to collect both case reports and case series on COVID-19 published up to April 24, 2020. There were no restrictions regarding publication language. Results: Eighty articles were included analyzing a total of 417 patients with a mean age of 48 years. The most common presenting symptom in patients who tested positive for COVID-19 was fever, reported in up to 62% of patients from 82% of the analyzed studies. Other symptoms including rhinorrhea, dizziness, and chills were less frequently reported. Additionally, in studies that reported C-reactive protein (CRP) measurements, a large majority of patients displayed an elevated CRP (60%). Progression to acute respiratory distress syndrome (ARDS) was the most common complication of patients testing positive for COVID-19 (21%). CT images displayed ground-glass opacification (GGO) patterns (80%) as well as bilateral lung involvement (69%). The most commonly used antiviral treatment modalities included, lopinavir (HIV protease inhibitor), arbidiol hydrochloride (influenza fusion inhibitor), and oseltamivir (neuraminidase inhibitor). Conclusions: Development of ARDS may play a role in estimating disease progression and mortality risk. Early detection of elevations in serum CRP, combined with a clinical COVID-19 symptom presentation may be used as a surrogate marker for the presence and severity of the disease. There is a paucity of data surrounding the efficacy of treatments. There is currently not a well-established gold standard therapy for the treatment of diagnosed COVID-19. Further prospective investigations are necessary.